Outcome of Decolonization Therapy in a Hospital in Southern Puerto Rico - Morales-Torres, Luisa; Rodríguez, Sharon; Toro, Jennifer; Lledo, Wanda; Ortiz, Carmen; Green, Vivian (Puerto Rico Health Sciences Journal, 2015)
Objective: Methicillin resistant Staphylococcus aureus (MRSA) is a resistant bacteria responsible for hard-to-treat infections. To understand the primary impact of this infection in healthcare settings, a retrospective study was performed at a hospital in southern Puerto Rico. Our objectives were to classify the types of MRSA infection, identify factors associated with the infection, and evaluate the outcome of decolonization therapy after its having been implemented at the hospital. Methods: Medical records of cases encompassing October 2009 through October 2011 were reviewed. A total of 761 MRSA -positive patients were identified and their infections classified as community-acquired MRSA (CA -MRSA), hospital-acquired MRSA (HA -MRSA), or healthcare-associated community-onset MRSA (HAC O-MRSA). Basic demographics, reason for hospitalization, medical history, and culture sites, along with other information, were obtained for each case. SPSS v17 was used for statistical analysis. Fisher’s exact test was used to measure the statistical significance of the crude OR, using the patients with CA -MRSA as the comparison group. HA - MRSA cases were compared before and after the intervention, using Epidat v4.0 to calculate the cumulative incidence of HA -MRSA before and after the implementation of decolonization therapy at the hospital. Results: In our study, 5.0% of the patients were found to be infected with HA -MRSA, 72.8%, with CA -MRSA, and 22.2%, with HAC O-MRSA . After the intervention, we found a decrease of 10.35% (p = 0.704) in HA -MRSA, of 2.6% (p = 0.791) in CA -MRSA, and of 7.0% in HACO-MRSA (p = 0.650). Conclusion: Our findings suggest that CA -MRSA could be responsible for the majority of the infections caused by MRSA within the hospital at which the study took place. Decolonization of MRSA is a useful tool in helping to control the spread of infection, although future studies are needed to confirm our study’s findings.